POSITIVE AND NEGATIVE AFFECTIVITY TOWARDS MANAGERIAL DECISION MAKING - Selvarajan, P.; Theebika, S. (Faculty of Graduate Studies, University of Sri Jayewardenepura, 2019)
This study investigates the importance of positive and negative affectivity on managerial decision making. A quantitative research study has been executed with a sample of 30 managerial level people by using purposive sampling method in an Apparel Company in Vavuniya, Sri Lanka. A questionnaire survey and personal interviewing methods have been used to get the appropriate responses from the required respondents. The correlation and multiple regression analyses were applied through SPSS version 20.0. The findings showed that there is a positive relationship between the positive affectivity and managerial decision making and a negative relationship between negative affectivity and managerial decision making. From these findings, the researchers recommend when there is a possibility to make a decision at the workplace, though it hurts the others, managers need to make the colleagues to understand the reality and accept it. Taking responsibility and giving responsibility to others would make wise and effective decisions. Further, controlling their emotions at workplace would be a good practice for the decision-makers and the other employees as well. Therefore, it is evident that the current research also supports the findings of the past literature which were investigated in different organisational settings in different countries.
Keywords: Emotions; Happiness; Managerial decision making; Negative affectivity; Positive affectivity